The Contribution of Native Public-Pedagogical Movement in Spreading the Ideas of the Physical Education of Youth (Late XX – Early XX c.) - Cherpak, Yuriy (Pedagogical Discourse, 2013)
The article studies the organizational and content aspects of sports associations in the context of public sports and recreation movement in the Ukrainian lands in the late XIX – early XX century. It says about the ways of physical education of children and youth in Kyiv and the territory of Dnieper Ukraine, demonstration of promoting ideas of physical education. It is found the differences in basic features of creation sports organizations. It is shown that the development of sport movement has contributed to social problems. Examples of regional (Kyiv) sports associations at the beginning of the twentieth century were describe here.